Development of industrial training assessment system (iTAS) 2.0: a step forward to educator 4.0 - Mohd Hanifa, Rafizah; Mohamad, Shamsul; Kamarudin, Muhammad Firdaus; Ramle, Rosni (Penerbit UTHM, 2020)
For many years, industrial training assessment at Universiti Tun Hussein Onn Malaysia (UTHM) is done using a paper-based system, which causes delay in entering marks, and significant cost incurred for printing, by the faculties and postage by the industries. To increase efficiency of the evaluation process, along with promoting green technologies and supporting green campus initiative, an online system named iTAS (Industrial Training Assessment System) 2.0 has been developed to allow industrial training students’ assessments to be executed online by internal (faculties) and external (industries) supervisors. iTAS 2.0 is designed as a user friendly multiplatform web-based system. Faculty and industrial supervisors complete their respective online assessment rubric in iTAS 2.0, which will then automatically calculate the industrial training marks for each student. In developing iTAS 2.0, System Development Life Cycle has been used. Implementation of iTAS 2.0 has indeed resulted in increased efficiency through significant reduction in time and cost by eliminating the amount of printing, physical transfer, and human error in calculation of marks. This effort could also raise UTHM’s UI Green Metric World University Ranking.